A 12-Week Cycling Training Regimen Improves Upper Limb Functions in People With Parkinson’s Disease - Nadeau, Alexandra; Lungu, Ovidiu; Boré, Arnaud; Plamondon, Réjean; Duchesne, Catherine; Robillard, Marie-Ève; Bobeuf, Florian; Lafontaine, Anne-Louise; Gheysen, Freja; Bherer, Louis; Doyon, Julien (Frontiers in Human Neuroscience, 2018)
Background: It has been proposed that physical exercise can help improve upper limb functions in Parkinson’s disease (PD) patients; yet evidence for this hypothesis is limited Objective: To assess the effects of aerobic exercise training (AET) on general upper limb functions in sedentary people with PD and healthy adults (HA). Methods: Two groups, 19 PD patients (Hoehn & Yahr ≤2) and 20 HA, matched on age and sedentary level, followed a 3-month stationary bicycle AET regimen. We used the kinematic theory framework to characterize and quantify the different motor control commands involved in performing simple upper-limb movements as drawing lines. Repeated measures ANCOVA models were used to assess the effect of AET in each group, as well as the difference between groups following the training regimen. Results: At baseline, PD individuals had a larger antagonist response, a longer elapsed time between the visual stimulus and the end of the movement, and a longer time of displacement of the stylus than the HA. Following the 12-week AET, PD participants showed significant decreases of the agonist and antagonist commands, as well as the antagonist response spread. A significant group*session interaction effect was observed for the agonist command and the response spread of the antagonist command, suggesting a significant change for these two parameters only in PD patients following the AET. Among the differences observed at baseline, only the difference for the time of movement remained after AET. Conclusion: A 3-month AET has a significant positive impact on the capacity to draw lines in a more efficiency way, in PD patients, indicating an improvement in the upper limb motor function.